2018
DOI: 10.1021/acs.jpclett.8b01242
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Relationship of Phenylene-Based Self-Assembled Monolayers for Record Low Work Function of Indium Tin Oxide

Abstract: Studying the structure-property relations of tailored dipolar phenyl and biphenylphosphonic acids, we report self-assembled monolayers with a significant decrease in the work function (WF) of indium-tin oxide (ITO) electrodes. Whereas the strengths of the dipoles are varied through the different molecular lengths and the introduction of electron-withdrawing fluorine atoms, the surface energy is kept constant through the electron-donating N, N-dimethylamine head groups. The self-assembled monolayer formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…6,7 To achieve a maximum work function shift (WFS), the molecular dipole has to be perpendicular to the surface. [8][9][10] Additionally, spatial and lateral control of the SAM's functional group is crucial for many single-molecule devices such as molecular wires, switches, rotors, sensors or redox-active or photochromic moieties. [11][12][13][14][15][16][17][18][19][20][21] Multipods allow generally a reasonable control of molecular orientation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 To achieve a maximum work function shift (WFS), the molecular dipole has to be perpendicular to the surface. [8][9][10] Additionally, spatial and lateral control of the SAM's functional group is crucial for many single-molecule devices such as molecular wires, switches, rotors, sensors or redox-active or photochromic moieties. [11][12][13][14][15][16][17][18][19][20][21] Multipods allow generally a reasonable control of molecular orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all atoms are arranged in such a way that the unit-cell axes of the packing arrangement remain unchanged within the domain itself. Benneckendorf et al [47] reported the structure-property relationships of dipolar phenyl and biphenylphosphonic acid: the strengths of the dipoles are varied through the inclusion of electron-withdrawing fluorine atoms and the molecular length, however, the surface energy is kept constant through the electron-donating N,N-dimethylamine fragment, which were able to form self-assembled monolayers on indium-tin oxide (ITO) electrodes modifying its work function (∅). In addition, quantum mechanical calculations showed that the dipole vector of N,Ndimethylaniline derivatives is orientated towards the electrode interface, directly influencing changes of the ∅ value [47].…”
Section: Resultsmentioning
confidence: 99%
“…Benneckendorf et al [47] reported the structure-property relationships of dipolar phenyl and biphenylphosphonic acid: the strengths of the dipoles are varied through the inclusion of electron-withdrawing fluorine atoms and the molecular length, however, the surface energy is kept constant through the electron-donating N,N-dimethylamine fragment, which were able to form self-assembled monolayers on indium-tin oxide (ITO) electrodes modifying its work function (∅). In addition, quantum mechanical calculations showed that the dipole vector of N,Ndimethylaniline derivatives is orientated towards the electrode interface, directly influencing changes of the ∅ value [47]. Meanwhile, by removing the methyl groups from the amino fragment, from NMe2 in 1 (quadrupolar) to NH2 in 2 (dipolar), the work function of the metal surfaces has been modified by the adsorption of SAMs, which form surface dipoles [48], as observed for 1 but also for the dithiolylidene-substituted carbo-quinoid 3.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been observed that organic dipole layers on Au and Ag reduced their WF, and a linear relationship existed between the size of the surface dipole moment and WF [43]. It has also been reported that the WF of an indium-tin oxide electrode could be reduced if the dipole vector due to a self-assembled monolayer (SAM) is pointing away from the electrode-SAM interface [44]. In the context of the current results, this suggests a general design principle for decreasing the WF of alloy surfaces by engineering structures with large interatomic charge transfer and surface dipoles.…”
Section: Cu 13 Ba Surfacesmentioning
confidence: 99%